E-Counseling Development Prototype as an Effort to Handle Student Mental Health and Student Academic Functions - Susilawati, Susilawati; Mulawarman, Mulawarman; Ahmadi, Farid (Scidacplus, 2024)
Mental health is an essential thing to pay attention to; mental health problems can attack all levels of society and can cause many victims for individuals, families and students and students. The Covid-19 pandemic is currently still affecting the whole world. Because of this, during the COVID-19 pandemic, many researchers paid more explicit attention to human mental health conditions. During the current COVID-19 pandemic, many students are experiencing mental health problems, including learning stress. Still, guidance and counseling services are also experiencing obstacles because they have to maintain health protocols, making it very difficult to provide face-to-face counseling. Cybercounseling So far, a lot of this has been done using applications such as Zoom, Google Meet, WhatsApp, Facebook, and Skype so that this research will develop a mobile application specifically for guidance and counseling. E-Counseling to produce an application that can meet user needs, the method used is ADDIE, where this method prioritizes design based on user needs. However, in this article, the stages only reach the design process.